The institutional gear as an element of systemic approach to innovation in Latin America - Borges-Quiñones, Marisol (Universidad Autónoma de Tamaulipas, 2018)
The systemic approach to innovation highlights the interrelationship between actors and institutions, but does not recognize the institutional complementarity. For that, this paper aims to design and assess an indicator of “institutional gear” as an element that recognizes the impact that an institution has over another in the innovation process, and the relationship between institutional gear index and economic growth. Linear regression was used by considering GDP per capita of 17 Latin American economies for the 1980 to 2014 period. Variables such as the rate of entrepreneurial activity (REA) which measures population in- volved, the percentage of REA that a new product or service has, effective government, state rights, laws and stable links between university-companies were used. These were classified as outputs and inputs. The institutional gear design was suitable for recognizing the complementary between the institutions and their role in innovation processes, as well as establishing that the countries where they have greater institutional gear have higher economic growth. The results show that the Latin American countries must boost the institutional gear to strengthen their national innovation systems and thus achieve sustained economic growth, as that shown by most of the developed countries (European Union and the United States).